2018
DOI: 10.1111/1467-6427.12251
|View full text |Cite
|
Sign up to set email alerts
|

Measuring competence in systemic practice: development of the ‘Systemic Family Practice – Systemic Competency Scale’ (SPS)

Abstract: Ensuring that practitioners are competent in the therapies they deliver is important for training, therapeutic outcomes and ethical practice. The development of the Systemic Practice Scale (SPS) is reported -a measure to assess the competence of novice systemic practitioners trialed by Children and Young Person's Improving Access to Psychological Therapies (CYP-IAPT) training courses. Initial reliability assessment of the SPS with twenty-eight supervisors of systemic practice evaluating students' competence us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 26 publications
(21 reference statements)
0
13
0
Order By: Relevance
“…Treatment skills, such as offering reflecting teams, will need to draw on new ways to monitor the impact of reflections on family members. The most common tool for assessing systemic skills in training is the Systemic Practice Scale (SPS, Butler et al ., 2020), which will also need to be extended to include digital practice.…”
Section: Applying a Digital Lens To Existing Systemic Competencies Frmentioning
confidence: 99%
“…Treatment skills, such as offering reflecting teams, will need to draw on new ways to monitor the impact of reflections on family members. The most common tool for assessing systemic skills in training is the Systemic Practice Scale (SPS, Butler et al ., 2020), which will also need to be extended to include digital practice.…”
Section: Applying a Digital Lens To Existing Systemic Competencies Frmentioning
confidence: 99%
“…Some have suggested that competence-based training challenges this systemic paradigm of interaction and locates competence solely within the individual irrespective of the context (Simon, 2010;Sutherland et al, 2012). Simon (2010) discusses the challenges systemic supervisors have working in training courses that are 'dominated by inflexible professional narratives' (p. 308) that may not fit within a culture where micro-measurement of clinical practice has become the norm (Butler et al, 2018;Tweed et al, 2010). Sutherland et al (2012) argued from a social constructionist perspective that 'what is "noticed" will depend in part on the observer's theoretical and philosophical commitments' (p. 3).…”
Section: Competence-based Practice and The Systemic Contextmentioning
confidence: 99%
“…The systemic practice scale (SPS) 1 was developed in response to current changes in the delivery of mental health services for children's and young persons' IAPT (CYP-IAPT) and the lack of measures to assess systemic competence (Butler et al, 2018). It is used in CYP-IAPT systemic family practice (SFP) courses across the UK, providing a structured assessment of systemic skills that can be used in supervision or as a training tool (Butler et al, 2018, Supporting Information).…”
Section: Competence-based Practice and The Systemic Contextmentioning
confidence: 99%
See 2 more Smart Citations